The Pinnotheridae of the northeastern Pacific (Alaska to Mexico): zoogeographical remarks and new bivalve hosts (Crustacea, Brachyura, Pinnotheridae) - Campos, Ernesto (Zootaxa, 2016)
New bivalve host records for four pinnotherid crabs of the Mexican Pacific are reported: Fabia subquadrata Dana, 1851, in Modiolus capax (Conrad, 1837); Opisthopus transversus Rathbun, 1893, in Tivela stultorum (Mawe, 1823); Pinnaxodes gigas (Green, 1992), in Pinna rugosa (Sowerby, 1835), and Panopea generosa Gould, 1850; and Tumidotheres margarita (Smith, 1870), in Nodipecten subnodosus (Sowerby, 1835). The southernmost distribution of F. subquadrata is extended to about 600 km along the west coast of the Baja California Peninsula; the distribution of P. gigas is extended outside the Gulf of California more than 1000 km north to San Quintín, on the west coast of Baja California; and the range of T. margarita is restricted on the west coast of Baja California to Scammon´s Lagoon, Baja California Sur and Playa Kino Viejo, Sonora in the central region of the Gulf of California, Mexico to Panama. Based on the new material, new information on taxonomy, ecology, and life history is provided for each of these species. Pinnotheres nudus Holmes, 1895 is restored as a valid species and is removed from its synonymy with O. transversus. An updated checklist with remarks on zoogeography for the 60 pinnotherid species, included in 23 genera, of the northeastern Pacific region (Alaska to the Mexican tropical Pacific) is given.